Causal relationship between particulate matter 2.5 and hypothyroidism: A two-sample Mendelian randomization study - Zhang, Yuning; Liu, Shouzheng; Wang, Yunwen; Wang, Yue (Frontiers in Public Health, 2022)
Background Epidemiological surveys have found that particulate matter 2.5 (PM2.5) plays an important role in hypothyroidism. However, due to the methodological limitations of traditional observational studies, it is difficult to make causal inferences. In the present study, we assessed the causal association between PM2.5 concentrations and risk of hypothyroidism using two-sample Mendelian randomization (TSMR). Methods We performed TSMR by using aggregated data from genome-wide association studies (GWAS) on the IEU Open GWAS database. We identified seven single nucleotide polymorphisms (SNPs) associated with PM2.5 concentrations as instrumental variables (IVs). We used inverse-variance weighting (IVW) as the main analytical method, and we selected MR-Egger, weighted median, simple model, and weighted model methods for quality control. Results MR analysis showed that PM2.5 has a positive effect on the risk of hypothyroidism: An increase of 1 standard deviation (SD) in PM2.5 concentrations increases the risk of hypothyroidism by 10.0% (odds ratio 1.10, 95% confidence interval 1.06–1.13, P = 2.93E-08, by IVW analysis); there was no heterogeneity or pleiotropy in the results. Conclusion In conclusion, increased PM2.5 concentrations are associated with an increased risk of hypothyroidism. This study provides evidence of a causal relationship between PM2.5 and the risk of hypothyroidism, so air pollution control may have important implications for the prevention of hypothyroidism.